Achievements of Numeracy Abilities to Children with Down Syndrome: Psycho-Pedagogical Implications. (13th May 2015) - Agheana, Viorel; Duţă, Nicoleta
Abstract: The paper addresses the issue of children with Down syndrome and psycho-pedagogical implications in the present. Down syndrome is the most common biological cause of intellectual disability. This intervention study was conducted to explore the effectiveness of using the tablet as a learning tool in teaching mathematics to children with Down syndrome. Also, to explore the extent to which children with Down syndrome are able to learn counting elementary mathematics concepts, such as the addition operation or subtraction. The results showed that there was significant progress in terms of basic mathematical skills acquisition in children who use electronic media than children who used only concrete objects. Research indicate that good teaching, using the children's strengths for visual learning lead us to conclusion that children with Down syndrome are able to learn and, in particular counting, if they are exposed to the appropriate conditions, which match their needs. Children with Down syndrome can improve their mathematical thinking skills through training that combines real activities with objects, math aps for tablet and visual configurations of numbers.